eHealth Literacy 3.0: Updating the Norman and Skinner 2006 Model - Ariesta Milanti; Cameron Norman; Dorothy Ngo Sheung Chan; Winnie Kwok Wei So; Harvey Skinner (Journal of Medical Internet Research)
This paper advances the “eHealth Literacy 3.0” model following Norman and Skinner’s 2006 original eHealth literacy 1.0 model and Norman’s 2011 2.0 update, and introduces a corresponding revision to the eHealth Literacy Scale (eHEALS) measurement instrument (eHEALS-R).